Characteristics Associated With Nonreceipt of Surveillance Testing and the Relationship With Survival in Stage II and III Colon Cancer. Issue 2 (9th September 2020) - Hines, Robert B; Jiban, Md Jibanul Haque; Lee, Eunkyung; Odahowski, Cassie L; Wallace, Audrey S; Adams, Spencer J E; Rahman, Saleh M M; Zhang, Shunpu
Abstract: We investigated characteristics of patients with colon cancer that predicted nonreceipt of posttreatment surveillance testing and the subsequent associations between surveillance status and survival outcomes. This was a retrospective cohort study of the Surveillance, Epidemiology, and End Results database combined with Medicare claims. Patients diagnosed between 2002 and 2009 with disease stages II and III and who were between 66 and 84 years of age were eligible. A minimum of 3 years' follow-up was required, and patients were categorized as having received any surveillance testing (any testing) versus none (no testing). Poisson regression was used to obtain risk ratios with 95% confidence intervals for the relative likelihood of No Testing. Cox models were used to obtain subdistribution hazard ratios with 95% confidence intervals for 5- and 10-year cancer-specific and noncancer deaths. There were 16, 009 colon cancer cases analyzed. Patient characteristics that predicted No Testing included older age, Black race, stage III disease, and chemotherapy. Patients in the No Testing group had an increased rate of 10-year cancer death that was greater for patients with stage III disease (subdistribution hazard ratio = 1.79, 95% confidence interval: 1.48, 2.17) than those with stage II disease (subdistribution hazard ratio = 1.41, 95% confidence interval: 1.19, 1.66). Greater efforts are needed to ensure all patients receive the highest quality medical care after diagnosis of colon cancer.